Enhancing Cross border Crime Investigations through the Application of Mother tongue (Global Journal of Human-Social Science, 2024)
This article explores the benefits of using mothertongue languages in cross-border criminal investigations It highlights the importance of linguistic ability and cultural awareness in detecting international crimes Mother-tongue languages can improve information accuracy trust and communication However they can also lead to communication breakdowns language barriers and incorrect interpretation of evidence The article also discusses the challenges of using dominant languages such as resource requirements technology s role in multilingual communication and legal and ethical requirements The article concludes that embracing linguistic diversity in law enforcement can improve investigations promote cooperation and enhance community safety and security
Keywords: cross border crime; investigation techniques; language analysis; linguistic intelligence; multilingual law enforcement